Strategic partnering for developing new products - Millson, Murray R.
Murray R. Millson, S. P. Raj and David Wilemon describe a process for helping management to overcome problems associated with new product development alliances.
A four-stage process can help management answer the questions it must answer when forming partnerships to develop new products.
New product development (NPD) is becoming increasingly complex and costly. One consequence of this is that more companies are using various partnering arrangements to accomplish their innovative goals. This article presents a process that can impact the important decisions relating to the successful development of new products by partners. NPD partnering is not a discrete event but a maturation process involving several stages including awareness, exploration, commitment, and dissolution. Issues that require consideration during this partnering process include identifying both the originating firm's needs and the partner's needs, understanding the likely consequences of the relative size and capabilities of partners, and selecting the appropriate alliance strategy.
Keywords: Strategic partnering